Study on prevalence and risk factors of hypertension in rural field practice areas of Kurnool medical college, Kurnool - Sreedevi, A.; Rao, G. Visweswara; Divya, B. Sri; Prasanthi, B.; lakshmi, B. Bhagya; Rani, G.S. Bindu; Sowmya, C. N.; shireesha, C. Sony; Venkatesh, L. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension causes 1.86% mortality worldwide. Hypertension and its consequences is the 7th leading cause of death in India. In India the prevalence of hypertension is 30%. This study is an attempt to identify the persons suffering from hypertension and their risk factors. The objectives of the study was to identify high risk groups suffering hypertension, to study association of hypertension with socio-demographic factors and other variables and to educate/generate awareness among the people residing in study area. Methods:This study is a community based cross sectional study in rural field practice areas of Kurnool Medical College, Kurnool from January-2015 to March-2015. The study population includes all the persons aged 35 and above. The sample size was 233. Two villages were selected from field practice area of Kurnool Medical College based on simple random sampling technique. Recording of blood pressure of aged 35 years and above was done by using sphygmomanometer. If the person had hypertension, clinical examination was done to identify any complications. Results: 42.42% of study population has hypertension. Hypertension was significantly more common in the age group of 41-60 years and significantly more among males. Hypertension was more common in professional and semiprofessional occupation, significantly more among population having BMI more than 25 KG/M2. Hypertension was significantly more common in smokers and non-vegetarians. Conclusions:As age progresses the prevalence of hypertension also increases. Hypertension was more common among male population. Hypertension was increased with BMI. Hypertension was more among persons with habits like smoking, alcoholism and non-vegetarians, persons using ghee. One fifth of the study population knew about symptoms and signs of hypertension. Half of the study population was known hypertensive and had regular health checkups and only one third had regular treatment. One tenth of study population knew about complications of untreated hypertension and no one was practicing stress relieving exercises.